(untitled) (Singaporean Journal of Business Economics and Management, 2019)
This article includes two sections: in the first section, theoretical basics about disclosure have been dealt with. It is said that disclosure is a relative concept. After finding out that financial information is presented for whom and for what purpose, disclosure should be considered as one of the fundamental goals of restatement of financial statements. The most relevant financial information should be presented in summary and if possible, in financial statements and then in notes attached to foregoing statements. Descriptive information should be mentioned in financial statements precisely and in summary and details should be described by notes attached to mentioned statements. Literature review is stated in the second section. It contains both internal and external related studies to the research subject.